2016
DOI: 10.3389/fphar.2016.00397
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking-Induced Cardiac Hypertrophy, Vascular Inflammation and Injury Are Attenuated by Antioxidant Supplementation in an Animal Model

Abstract: Background: Cardiovascular diseases are the leading causes of morbidity and mortality worldwide. Cigarette smoking remains a global health epidemic with associated detrimental effects on the cardiovascular system. In this work, we investigated the effects of cigarette smoke exposure on cardiovascular system in an animal model. The study then evaluated the effects of antioxidants (AO), represented by pomegranate juice, on cigarette smoke induced cardiovascular injury. This study aims at evaluating the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 47 publications
0
43
0
1
Order By: Relevance
“…Accordingly, our findings may refer to a potential absorptive effect of cigarette smoking and/or moderate coffee consumption (MCC) on the negative consequences of excessive consumption of coffee as shown in the combined effect of both factors by the results of two-way ANOVA test. However, hyperlipidemic levels of LDL-C and TC have been correlated with the separate effect of HCC and cigarette smoking in humans 18,27,28 and animal models. [29][30][31][32] Nevertheless, some studies showed that caffeine has significant effects 11,23 or no effect on the lipid profile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, our findings may refer to a potential absorptive effect of cigarette smoking and/or moderate coffee consumption (MCC) on the negative consequences of excessive consumption of coffee as shown in the combined effect of both factors by the results of two-way ANOVA test. However, hyperlipidemic levels of LDL-C and TC have been correlated with the separate effect of HCC and cigarette smoking in humans 18,27,28 and animal models. [29][30][31][32] Nevertheless, some studies showed that caffeine has significant effects 11,23 or no effect on the lipid profile.…”
Section: Discussionmentioning
confidence: 99%
“…17 Correspondingly, the association of cigarette smoking with CVDs can be attributed to increased oxidative stress due to excessive free radicals resulted from burning tobacco and other chemicals of the cigarettes. 18,19 Nicotine, which is the main component of cigarette smoke, causes coronary death by provoking ventricular arrhythmias. Cardiac effects of nicotine happen due to the stimulation of nicotinic receptor, which enhances the release of catecholamine.…”
Section: Introductionmentioning
confidence: 99%
“…A vast array of evidence indicates that excessive ROS production, exceeding the anti-oxidative capacity of cells, may damage cell components such as DNA, protein, and lipids, and then cause cellular dysfunction [20]. Meanwhile, a number of adverse events associated with oxidative stress are observed in tissues following CSE, which include cardiac hypertrophy [21], pulmonary fibrosis [22] as well as endothelial cells injury [23]. In mammalian cells, ROS is scavenged by a host of enzymatic antioxidants including superoxide dismutase (SOD), catlase (CAT) and glutathione peroxidase (GPx), and nonenzymatic antioxidants, such as glutathione (GSH) [20,24].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, the effects of pomegranate juice concentrate (equivalent to 80 μmol polyphenols/mL) were measured on cigarette smoking‐induced‐cardiac hypertrophy in rats. It has been demonstrated that pomegranate juice mitigates the ROS level, ObR, and Fn1 fibrotic markers, Bdkrb1 and Bdkrb2 kinin receptor, IL‐1β and TNF‐α expression level in aorta of rats (Al Hariri et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…In another study, the effects of pomegranate juice concentrate (equivalent to 80 μmol polyphenols/mL) were measured on cigarette smoking-induced-cardiac hypertrophy in rats. It has been demonstrated that pomegranate juice mitigates the ROS level, ObR, and Fn1 fibrotic markers, Bdkrb1 and Bdkrb2 kinin receptor, IL-1β and TNF-α expression level in aorta of rats(Al Hariri et al, 2016).Cornélio Favarin et al evaluated the effects of EA (10 mg/kg; orally) in the ALI induced by spitting acid in the left lung of mice. EA attenuated the permeability of blood vessels and the number of neutrophils in BALF.…”
mentioning
confidence: 99%